Formation of tubular conduction channel in a SiGe(P)/Si core/shell nanowire heterostructure - Xuejing Wang; Yung-Chen Lin; Chia-Tse Tai; Seok Woo Lee; Tzu-Ming Lu; Sun Hae Ra Shin; Sadhvikas J. Addamane; Chris Sheehan; Jiun-Yun Li; Yerim Kim; Jinkyoung Yoo (APL Materials, 2022)
Realizing a tubular conduction channel within a one-dimensional core–shell nanowire (NW) enables better understanding of quantum phenomena and exploration of electronic device applications. Herein, we report the growth of a SiGe(P)/Si core/shell NW heterostructure using a chemical vapor deposition coupled with vapor–liquid–solid growth mechanism. The entire NW heterostructure behaves as a p-type semiconductor, which demonstrates that the high-density carriers are confined within the 4 nm-thick Si shell and form a tubular conduction channel. These findings are confirmed by both calculations and the gate-dependent current–voltage (Id–Vg) characteristics. Atomic resolution microscopic analyses suggest a coherent epitaxial core/shell interface where strain is released by forming dislocations along the axial direction of the NW heterostructure. Additional surface passivation achieved via growing a SiGe(P)/Si/SiGe core/multishell NW heterostructure suggests potential strategies to enhance the tubular carrier density, which could be further modified by improving multishell crystallinity and structural design.